Potential Long-Term Complications of Endovascular Stent Grafting for Blunt Thoracic Aortic Injury - Larry E. Miller (The Scientific World Journal, 2012)
Blunt thoracic aortic injury (BTAI) is a rare, but lethal, consequence of rapid deceleration events. Most victims of BTAI die at the scene of the accident. Of those who arrive to the hospital alive, expedient aortic intervention significantly improves survival. Thoracic endovascular aortic repair (TEVAR) has been accepted as the standard of care for BTAI at many centers, primarily due to the convincing evidence of lower mortality and morbidity in comparison to open surgery. However, less attention has been given to potential long-term complications of TEVAR for BTAI. This paper focuses on these complications, which include progressive aortic expansion with aging, inadequate stent graft characteristics, device durability concerns, long-term radiation exposure concerns from follow-up computed tomography scans, and the potential for (Victims of Modern Imaging Technology) VOMIT.